Religious Digital Literacy among Islamic Boarding School Students through a Critical Study of the Salafiyah Islamic Boarding School Curriculum - Mahmudah, Siti; Ridwan, Iwan (West Science Islamic Studies, 2025)
This study examines religious digital literacy among Islamic boarding school students through a critical analysis of the Salafiyah Islamic boarding school curriculum. Using a qualitative research approach, data were collected from five informants consisting of teachers, students, and curriculum administrators through in-depth interviews, participant observations, and document analysis. The findings reveal that while Salafiyah pesantren maintain a strong emphasis on traditional religious learning based on classical texts (kitab kuning), there is a growing awareness among teachers and students of the importance of digital literacy in strengthening religious understanding and critical thinking. However, the integration of digital literacy remains limited due to concerns over maintaining moral discipline, lack of digital infrastructure, and insufficient teacher training. The study identifies key challenges such as the tension between preserving traditional values and adapting to technological advancements. It also highlights opportunities for developing a contextualized digital literacy framework grounded in Islamic ethics. The results suggest that religious digital literacy in Salafiyah pesantren can serve as a bridge between faith-based education and the demands of the digital era, promoting responsible digital engagement while preserving religious authenticity.